Oligopoly Power, Cross-Market Effects and Demand Relatedness: An Empirical Analysis (European Journal of Marketing and Economics, 2023)
The goal of the paper is to develop a conceptual framework that can be used to examine market competitiveness and assess cross-market effects in a multi-product oligopoly consisting of firms producing and selling various demand-related products. The econometric model which consists of two inverse demand functions and two price-margin equations is applied to the US catfish processing industry. Focusing on fresh catfish filet and whole fresh catfish, the empirical results rule out the existence of cross-market effects, but give support to the existence of some degree of market power. In that setting, the oligopoly power indices are, respectively, 18.2% and 13.3% for fresh catfish filet and whole fresh catfish thereby indicating that the price distortion is more pronounced in the market for fresh catfish filet than it is in the market for whole fresh catfish.
Keywords: Oligopoly power, Cross-market Effects, Multi-product firms.